Використання елементів психології у дизайні сайтів - Цигічко, М. В. (ХНУРЕ, 2021)
The paper considers some elements of a high-quality and user-friendly interface for a mobile or web application, which are based on the prin ciples of psychology and emotional perception of design. This problem belongs to the field of activity of specialists in UI (interface design) and UX (user experience). These recommendations can enhance the impact of scientifically sound methods and techniques for building and testing the quality of the created interface.
Keywords: психологія у дизайні сайтів; елемент психології